Acceptance in the Teaching Practice course as a potential for reflective dialogues for undergraduates of a Chemistry course (Research, Society and Development, 2022)
Chemistry undergraduate students experience a technical academic culture, focused on specific knowledge, however, at the end of graduation, many of them will act as Chemistry teachers in schools where welcoming is essential and necessary. This work aims to reflect on the impressions of undergraduates in Chemistry on the use of moments of welcome in the subject of Teaching Practice. For that, a qualitative and descriptive case study was developed with 14 students of a Licentiate Degree in Chemistry in Ceará. Students consented to participate by signing the term, in compliance with Resolution 466/2012. Data collection was carried out through the records of comments and questionnaire application, after the application of the welcomes during eight meetings between April and July 2021. The analysis of the responses showed that 100% of the students revealed that the welcomes were relevant for the conduct of the discipline, there were also expressions of anxieties, doubts about the profession, sharing of experiences, identification with everyday situations presented. The reflections that submerged from the comments were listed in important elements of pedagogical practice, such as: motivation, teaching and learning characteristics, teaching innovation, planning, the role of pedagogical subjects in teacher education, the dialogical process also provided by the identification of knowledge students', overcoming the challenges in teacher training. Therefore, it can be concluded that the receptions provided reflections on the profession and its implications, strengthening an identification of the undergraduates as future chemical educators.